Investigation of antioxidant activity of new xanthine xenobiotics - Mуkhalchenko, Ye. K.; Vasyliyev, D. A.; Михальченко, Євген Костянтинович; Васильєв, Денис Андрійович (Poltava : Ukrainian Medical Stomatological Academy, 2021)
Relevance: Recent studies have shown that in the pathogenesis of most diseases (cardiovascular, nervous, liver, lung diseases), which determine the main rate of mortality and disability, oxidative stress plays an important role. The latter includes free radical (FRO) and peroxide oxidation, leading to membrane damage and cell death. The search for antioxidant compounds that can decrease pathological biochemical processes by oxidative stress and, consequently, can provide a prophylactic and therapeutic effect, is very important for modern medicine. Therefore, pharmacological agents for metabolic correction of conditions caused by oxidative stress need to be intensively developed. Synthetic drugs with antioxidant properties, like xanthine xenobiotics, are attracting more and more attention of scientists.
Keywords: Xanthine; antioxidant activity; oxidation